The Impact of Using the Imagidice Board Game on Improving Basic Grammar Skills in EFL Learners - Chun-Fu Chen (Yayasan Visi Intan Permata, 2025)
Grammar is a crucial yet challenging aspect of acquiring a second language. Many English as a Foreign Language (EFL) learners find grammar lessons overwhelming, especially when taught through traditional methods that rely heavily on rule explanation and repetitive drills. Disengagement or arrested language development may follow. To help address this, educators are increasingly incorporating interactive tools, such as board games, into lessons to create a more engaging learning environment. Board games have become increasingly diverse, with each game’s functionality based on its specific design purpose. This original research investigates the effect of a solely image-based board game, Imagidice, on the basic grammar skills among some young EFL learners. The Imagidice game is a versatile and innovative tool for language instruction, offering flexible application across multiple grammar and speaking activities. The research was conducted with 18 learners aged 10 to 12 at a cram school in Taiwan. Over six weeks, participants engaged in 12 grammar-focused game activities, conducted twice weekly in 40-minute sessions. A mixed-methods approach was used, including pre- and post-tests, classroom observations, questionnaires, and teacher interviews. Results showed a statistically significant improvement in learners’ grammar performance. Learners’ mean scores increased from 57.06 (SD = 10.65) on the pre-test to 82.69 (SD = 8.77) on the post-test. Learners also expressed increased motivation and enjoyment during the lessons. The game facilitated natural interaction with grammar structures, stimulated creativity, and enhanced vocabulary retention. The visual prompts helped reduce language anxiety and supported more confident expression. To enhance generalisability, future research would benefit from increased sample size, varied classroom contexts, and duration of instruction. Further, comparative studies examining the effectiveness of Imagidice in relation to other games could help provide insights into best practices in gamified EFL instruction.